C. elegans AMPKs promote survival and arrest germline development during nutrient stress - Masamitsu Fukuyama; Kensuke Sakuma; Riyong Park; Hidefumi Kasuga; Ryotaro Nagaya; Yuriko Atsumi; Yumi Shimomura; Shinya Takahashi; Hiroaki Kajiho; Ann Rougvie; Kenji Kontani; Toshiaki Katada (Biology Open, 2012)
Summary Mechanisms controlling development, growth, and metabolism are coordinated in response to changes in environmental conditions, enhancing the likelihood of survival to reproductive maturity. Much remains to be learned about the molecular basis underlying environmental influences on these processes. C. elegans larvae enter a developmentally dormant state called L1 diapause when hatched into nutrient-poor conditions. The nematode pten homologue daf-18 is essential for maintenance of survival and germline stem cell quiescence during this period (Fukuyama et al., 2006; Sigmond et al., 2008), but the details of the signaling network(s) in which it functions remain to be elucidated. Here, we report that animals lacking both aak-1 and aak-2, which encode the two catalytic α subunits of AMP-activated protein kinase (AMPK), show reduced viability and failure to maintain mitotic quiescence in germline stem cells during L1 diapause. Furthermore, failure to arrest germline proliferation has a long term consequence; aak double mutants that have experienced L1 diapause develop into sterile adults when returned to food, whereas their continuously fed siblings are fertile. Both aak and daf-18 appear to maintain germline quiescence by inhibiting activity of the common downstream target, TORC1 (TOR Complex 1). In contrast, rescue of the lethality phenotype indicates that aak-2 acts not only in the intestine, as does daf-18, but also in neurons, likely promoting survival by preventing energy deprivation during L1 diapause. These results not only provide evidence that AMPK contributes to survival during L1 diapause in a manner distinct from that by which it controls dauer diapause, but they also suggest that AMPK suppresses TORC1 activity to maintain stem cell quiescence.